Participation of Citizens in the Maintenance of Public Order Historical-Theoretical Significance (Journal of Pedagogical Inventions and Practices, 2022)
This article shows how the participation of citizens in the maintenance of Public Order was formed from a historical point of view and how such processes took place on the example of other states. Also, the current problems in the wider involvement of citizens and proposals for their solution are outlined.